Acute Gastrocnemius-Soleus Complex Injuries in National Football League Athletes. Issue 1 (25th January 2017) - Werner, Brian C.; Belkin, Nicole S.; Kennelly, Steve; Weiss, Leigh; Barnes, Ronnie P.; Potter, Hollis G.; Warren, Russell F.; Rodeo, Scott A.
Background: Lower extremity muscle injuries are common in professional football. Although less common than hamstring or quadriceps injuries in National Football League (NFL) athletes, calf injuries occur with relative frequency and have not previously been studied. Purpose: To evaluate gastrocnemius-soleus complex muscle injuries over the past 13 years from a single NFL team to determine the incidence of such injuries, their imaging characteristics, and return to play after such injuries and any correlation between imaging findings and prolonged return to play. Study Design: Case series; Level of evidence, 4. Methods: A retrospective review of all acute calf muscle injuries on a single NFL team from 2003 to 2015 was performed. Player demographics and return-to-play data were obtained from the medical records. All available magnetic resonance images (MRIs) were reviewed by a musculoskeletal radiologist for specific imaging findings that correlated with return to play. Results: A total of 27 calf injuries in 24 NFL players were reviewed, yielding an incidence of 2.3 acute calf injuries per year on a single NFL team. Of these 27 injuries, 20 (74%) were isolated injuries to the gastrocnemius muscle, 4 (15%) were isolated injuries to the soleus muscle, and the remaining 3 injuries (11%) involved both. Defensive players were more likely to sustain injuries ( P = .043). The mean time to return to play for all 27 players was 17.4 ± 14.6 days (range, 3-62 days). MRIs were available in 14 of the 27 injuries. The average size of the fascial defect ( P = .032) and the presence of a fluid collection ( P = .031) both correlated with return to play of longer than 2 weeks. Conclusion: Although less common than hamstring or quadriceps muscle injuries, calf muscle injuries occur with relative frequency in the NFL, and more so in defensive players. The majority of these injuries occur in the gastrocnemius and result in significant disability, with at least 2 weeks of missed playing time on average. MRI may have an important role in the evaluation of calf injuries in NFL players, as certain injury imaging characteristics, including the anteroposterior size of any fascial tear and the presence of a fluid collection, are associated with longer return-to-play times after injury.